2020
DOI: 10.1186/s13071-020-04234-8
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS: optimization for future uses in entomological surveillance and identification of mosquitoes from New Caledonia

Abstract: Background: Mosquito vectors cause a significant human public health burden through the transmission of pathogens. Due to the expansion of international travel and trade, the dispersal of these mosquito vectors and the pathogens they carry is on the rise. Entomological surveillance is therefore required which relies on accurate mosquito species identification. This study aimed to optimize the use of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) for mosquito identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(72 citation statements)
references
References 29 publications
(64 reference statements)
6
66
0
Order By: Relevance
“…Indeed, with consideration of the highest scoring spectrum, the legs required the using of four replicates of protein extract whereas for the head, only one replicate provided almost equivalent results as using four replicates, at the LSV threshold of 1.7 and 1.8. These results are concordant with a recent study on mosquitoes [ 25 ] that observed that using the legs, the LSVs were improved when three spots of each sample were deposited onto the target plate, compared to the using of only one spot. Therefore, the using of the head will represent a concrete improvement of the routine use of MALDI-TOF for Anopheles identification, as it will allow to gain rapidity of analysis by decreasing the number of deposits.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Indeed, with consideration of the highest scoring spectrum, the legs required the using of four replicates of protein extract whereas for the head, only one replicate provided almost equivalent results as using four replicates, at the LSV threshold of 1.7 and 1.8. These results are concordant with a recent study on mosquitoes [ 25 ] that observed that using the legs, the LSVs were improved when three spots of each sample were deposited onto the target plate, compared to the using of only one spot. Therefore, the using of the head will represent a concrete improvement of the routine use of MALDI-TOF for Anopheles identification, as it will allow to gain rapidity of analysis by decreasing the number of deposits.…”
Section: Discussionsupporting
confidence: 92%
“…As previously mentioned [16], the fragility of the legs, which are breakable and can be lost during collection, transportation, storage or processing, may lead to partial or total loss of the protein content. Indeed, a study showed that legs were prone to degradation during the trapping, with modification of protein profiles and a decrease of identification log(scores) as the trapping duration increased, even after 24 h of trapping [25]. Similarly, disparities have been observed in this study, between spectra from laboratory-reared specimens and from field-caught specimens for every anatomic parts.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations